Investigation of Accelerated Salt Spray Corrosion on Mechanical Response of Al6061T6 and Al7075T6 Alloys - Kumar S, Sunil; V Londe, Neelakantha; Kumar K, Dilip; Kittur, Mohammed Ibrahim; Badruddin, Irfan Anjum; Mohammed Faheem; Khan, Sher Afghan (International Journal of Integrated Engineering, 2022)
Abstract: Accelerated corrosion by salt spray has been utilized on Al6061T6 and Al7075T6 aluminum alloys to evaluate the amount of degradation and the effect on mechanical behavior. Aluminum alloys were placed in a salt spray chamber for a period of 250 hours and 500 hours respectively. It was observed that the oxide layer was unprotective after prolonged salt spray resulting in pitting continued with exfoliation corrosion. The tensile test results show that there was a remarkable decrease in tensile properties with exposure time. There was a significant decrease in tensile strength, yield strength, elongation at yield, elongation at break and overall toughness in both the alloys at the end of 500 hours of exposure. The impact strength decreased by 14.4 % and 26.47 %, Rockwell hardness (HRB) reduced by 12.2% and 20.71% for respective alloys at 500 hours of exposure. However, there was an increasing trend in elastic stiffness which attributed to decrease in ductility. Further, it was comparatively observed that Al7075T6 is more susceptible to corrosion than Al6061T6. Keywords: Aluminum alloys, Pitting, Corrosion, Mechanical Properties.